2007
DOI: 10.1080/01904160701615467
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phosphatases, Iron Reducing, and Solubilizing Activity on the Nutrient Acquisition in Mixed Cropped Peanut and Barley

Abstract: The effect of interspecific complementary and competitive root interactions and rhizosphere effects on primarily phosphorus (P) and iron (Fe) but also nitrogen (N), potassium (K), calcium (Ca), zinc (Zn), and manganese (Mn) nutrition between mixed cropped peanut (Arachis hypogaea L.) and barley (Hordeum vulgare L.). In order to provide more physiological evidence on the mechanisms of interspecific facilitation, phosphatase activities in plant and rhizosphere, root ferric reducing capacity (FR), Fe-solubilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
1
3
0
1
Order By: Relevance
“…Among the vertical combinations, the maximum value of SMBC (175.9g/ kg) soil was recorded with turmeric + squash followed by turmeric+ sponge gourd. The soil biological activities are greatly influenced by the type of crops grown in the combinations, hence the results were in agreement with the finding of Gunes et al (2007). Thus, it can be concluded that the ecofriendly vertical cropping of turmeric with cucurbits is a viable alternative for sustaining the livelihood security of hill farmers.…”
Section: Resultssupporting
confidence: 86%
“…Among the vertical combinations, the maximum value of SMBC (175.9g/ kg) soil was recorded with turmeric + squash followed by turmeric+ sponge gourd. The soil biological activities are greatly influenced by the type of crops grown in the combinations, hence the results were in agreement with the finding of Gunes et al (2007). Thus, it can be concluded that the ecofriendly vertical cropping of turmeric with cucurbits is a viable alternative for sustaining the livelihood security of hill farmers.…”
Section: Resultssupporting
confidence: 86%
“…Our results are similar with this and other studies, which reported that cereal-legume IC increased the RS-APase activity compared to when either silage corn or forage soybean were cultivated as monocrops 7,47 . The legume species have been considered as the major contributor to the increased RS‒APase activity observed in IC due to the fact that large amounts of acid phosphatase are known to be released from their roots into the root rhizosphere 26,56 . This may account in part for the increase forage production observed in IC considering the significant correlations observed between RS‒APase activity, the RS‒P available and forage production (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Non-symbiotic N 2 fixation was not observed on the forest floor and in the upper soil layer at Kondi (Le Mer and Roger, 2001) and accounts for a low input of N (often (5 kg ha À1 year À1 ) in temperate forest ecosystems (Son, 2001). An attractive option to improve the N status of the soil might therefore be to introduce leguminous species in Eucalyptus plantations (Binkley et al, 2003) in order to fix atmospheric N 2 and possibly to promote orthophosphate mobilisation (Gunes et al, 2007). Fertilization is a major input of nutrients in most commercial Eucalyptus plantations established on highly weathered soils and, even though the amounts of fertilizer are usually low in comparison with tree requirements, the timing of the application and the localization of fertilizers considerably influence stand growth (e.g.…”
Section: Atmospheric Depositions Weathering Of Soil Minerals and Fermentioning
confidence: 99%